2022
DOI: 10.1039/d1dt03782j
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic photocatalytic effect of BiOBr–BiOI heterojunctions due to appropriate layer stacking

Abstract: In thin film heterojunctions the order of the layers is crucial to obtain a synergistic effect. The layout S-BiOI–BiOBr boosted the photocatalytic activity as light was completely used and the charges were favored to move to the surface and react.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…25 Moreover, Arana-Trenado, et al, showed that in thin film heterojunctions of BiOI-BiOBr, the order of the layers plays a crucial role in the photocatalytic response, finding that in one case the response is boosted, while in the opposite configuration is quenched. 26 However, none of these works focus on the influence of the thickness of each layer in the photocatalytic response of the heterojunctions. In fact, a typical position is to think that "since photocatalysis is a surface phenomenon, the outermost layer is the only one relevant for the process, and the internal layer is useless".…”
Section: Introductionmentioning
confidence: 99%
“…25 Moreover, Arana-Trenado, et al, showed that in thin film heterojunctions of BiOI-BiOBr, the order of the layers plays a crucial role in the photocatalytic response, finding that in one case the response is boosted, while in the opposite configuration is quenched. 26 However, none of these works focus on the influence of the thickness of each layer in the photocatalytic response of the heterojunctions. In fact, a typical position is to think that "since photocatalysis is a surface phenomenon, the outermost layer is the only one relevant for the process, and the internal layer is useless".…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Among them, BiOBr was paid much attention by scientists due to its appropriate band gap and advantages of non-toxicity, low cost and environmental friendliness. [18][19][20][21][22][23] In addition, it has a unique structure in which the [Bi 2 O 2 ] 2+ plates are sandwiched between the double Br − layers, which leads to easy breaking of the Bi-O bond to produce oxygen vacancies. 24 The oxygen vacancies improve the separation and transport of photogenerated charges which improve photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, constructing a heterojunction based on BiOBr to improve the absorption of visible light, promote the separation of photocarriers, and introduce porosity is highly desirable. 21–23…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, constructing a heterojunction based on BiOBr to improve the absorption of visible light, promote the separation of photocarriers, and introduce porosity is highly desirable. [21][22][23] Metal-organic frameworks (MOFs), as a new type of porous coordination polymer composed of organic ligands and metal nodes or metal clusters, have attracted more and more attention due to their unique porous structure, controllable pore size, large surface area, good thermal stability and high catalytic activity. [24][25][26] Some photoactive MOFs are photoresponsive and usually exhibit n-type semiconductor behavior by ligandto-metal charge transfer (LMCT) or direct excitation of metal nodes to generate charge separation states, and have been used as catalysts for photocatalytic reactions, such as photocatalytic water decomposition, [27][28][29] CO 2 reduction [30][31][32] and organic conversion.…”
Section: Introductionmentioning
confidence: 99%